Politik Uang Pada Pilkada Merangin Tahun 2024 - Salman, Salman; Suparta, Endang; Cantika, Fuji (Adagium: Jurnal Ilmiah Hukum, 2025)
Money politics is the biggest bugbear in every political recruitment, including in regional head elections (pilkada). Through the pilkada, it is expected that qualified regional leaders will be elected according to the will of the people, but in its implementation, one of the "democratic parties" is the display of fraudulent behavior, dishonesty, lies in the campaign and even fooling the public by giving money or goods before voting so that voters choose certain candidates known as money politics. The phenomenon of money politics in the implementation of the Regional Head Election (Pilkada) in Merangin Regency, which refers to the use of money or materials to influence voters' choices, has become a significant problem in the democratic process in Indonesia, including in the Merangin Pilkada. The results of the study show that money politics occurs in various forms, such as giving cash, goods, and political promises to voters and party cadres. Social, economic, and educational factors are the main triggers for the development of this practice. In addition, the practice of money politics threatens the integrity of the Pilkada by reducing the level of political participation of the community and reducing the accountability of regional head candidates. This article suggests the need to strengthen political supervision and education to minimize the negative impacts of money politics in elections and regional elections in Indonesia.